2015
DOI: 10.1097/md.0000000000001449
|View full text |Cite
|
Sign up to set email alerts
|

Association of Physical Performance and Pain With Fear of Falling Among Community—Dwelling Japanese Women Aged 65 Years and Older

Abstract: Our aim was to explore the association of physical performance and pain with fear of falling among community-dwelling Japanese women.The subjects were 278 women aged 65 years and over. We collected information on fear of falling, painful joints, comorbidities, falls in the previous year, and cataracts. Walking time (distance of 6 m), chair stand time (5 times), grip strength, the timed up and go test (TUG), and functional reach were measured.The prevalence of fear of falling was 36.3%, and it increased with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
3
23
1
2
Order By: Relevance
“…Although no statistical difference was found for FR in the study above presented (Tomita et al, 2015), results of this test in the present study also proved different between individuals from G1 and G3. In the same way, Lopes et al, (2009) found in their results correlation between fear of falling and the FR test, justified by inability or incapacity to perform this test, suggested by the presence of balance deficit, which may be linked to fear of falling.…”
Section: Resultscontrasting
confidence: 37%
See 2 more Smart Citations
“…Although no statistical difference was found for FR in the study above presented (Tomita et al, 2015), results of this test in the present study also proved different between individuals from G1 and G3. In the same way, Lopes et al, (2009) found in their results correlation between fear of falling and the FR test, justified by inability or incapacity to perform this test, suggested by the presence of balance deficit, which may be linked to fear of falling.…”
Section: Resultscontrasting
confidence: 37%
“…As a result, they found that TUG and SR5 showed different values between groups, corroborating with findings of the present study, which also found difference between individuals who were more and less afraid of falling. However, in the study by Tomita et al (2015), the Functional Reach test (FR) showed no statistical difference between groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yapılan çalışmalarda yaşlılarda düşme korkusu prevalansının %20-85 arasında değiştiği bildirilmektedir. (23)(24)(25)(26)(27)(28) Prevalanstaki bu farklılıkların düşme korkusu ölçüm yöntem-lerinden, düşme korkusunun tanımından, araştırılan toplumun özelliklerinden, yaş ve cinsiyet farklılıklarından kaynaklandığı düşünülebilir. Bizim çalışma sonucumuz da bahsedilen araştır-ma sonuçları ile benzerlik göstermekte olup, yaşlılarda düşme ve düşme korkusunun yaygın bir sorun olduğunu desteklemektedir.…”
Section: Discussionunclassified
“…Furthermore, its prevalence among the elderly population is substantially high. Many studies have reported that an average of 21-85% of the elderly population has FOF [5][6][7][8]. The various risk factors that have been identified to be associated with FOF are previous history of falling, impaired gait, imbalance, unsteadiness, muscle weakness and limitation of daily tasks [9,10].…”
Section: Introductionmentioning
confidence: 99%